EFL Teachers’ Challenges and Opportunities of Emergency Remote Teaching During The Covid-19 Pandemi C: Narrative Inquiry - Elis Sundarwati; Muhammad Reza Pahlevi (Universitas Pendidikan Ganesha, 2021)
This research aims to explore challenges and opportunities that EFL teachers have in emergency remote teaching during covid-19 pandemic in senior high school, Bogor. This study expects to be a consideration for future studies and policies regarding emergency remote teaching. This study employs narrative inquiry methods which explores objective experience of 4 EFL teachers. In this research the technique of collecting data researchers use interview and documentation. There are some general pattern findings that represent this study. The study discovered that there are technical and pedagogical challenges during emergency remote teaching. However, some opportunities submerged that benefits the teachers self development as teachers and digital skills which shows sign of self-sense and authority as teachers.